Pengaruh Penerapan Etika Bisnis Muhammad Saw Terhadap Customer Retention dan Dampaknya Terhadap Peningkatan Pendapatan Internal Stakeholders (Studi Kasus pada Unit Usaha Penjualan dan Jasa Penggilingan Daging Pelita Jaya Jember) - Siti Nur Latifah (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
This study aims to analyze the effect of the application of Muhammad Saw's Business Ethics to Customer Retention and Its Impact on Increasing Internal Stakeholder Income (Case Study in Pelita Jaya Jember Meat Sales and Milling Service Business Unit). The population in the study is all consumers who are not limited in number who are consumers in the Business Unit of Sales and Meat Milling Services of Pelita Jaya Jember, while the sampling in this study uses Quota Sampling techniques and Accidental Sampling, then set as many as 100 respondents with Accidental sampling techniques Sampling is a sampling procedure that selects samples from people or units that are easily found or accessed. This study uses Path Analysis or Path Analysis. Data were tested using the Classical Test for Normality, Heterocedasticity, Multicollinearity and Autocorrelation. Hypothesis testing is done using IBM SPSS Version 25.0. The results of the analysis show that the Business Ethics of Muhammad SAW (X) had a significant effect on Customer Retention (Z) with direct influence path coefficients of 0.566. Muhammad SAW's Business Ethics (X) has a significant effect on the Increase in Income of Internal Stakeholders (Y) with direct influence path coefficients of 0.154. In addition, Customer Retention (Z) also has a significant effect on the Increase in Income of Internal Stakeholders (Y) with direct effect path coefficients of 0.699. The indirect influence of Muhammad SAW's Business Ethics (X) on Increased Income of Internal Stakeholders (Y) through Customer Retention (Z) is significant with standardize coefficients of 0.395.